Perception of Medical Graduates Towards Anesthesiology: A Prospective Cross-Sectional Study - Pradhan, Rosi; Maharjan, Anil; Lamichhane, Bibena; Bhochhibhoya, Anisha; Shrestha, Samundra Kumar; Bhochhibhoya, Ashmita; Laudari, Uttam (Journal of Society of Surgeons of Nepal, 2022)
Introduction: Despite the availability of a number of specialties, only few areas come as a choice for post-graduation. The main purpose of this study was to determine the perception of undergraduate students towards anesthesiology and the factors that determine considering or not considering anesthesiology as a career. Methods: A questionnaire based cross-sectional study was conducted among medical interns at KIST Medical College in January 2018. Seventy interns participated in this study. The questionnaire sought information on their perception and reasons for considering or not considering anesthesiology. Results: Majority of the medical interns [58 (82.85%)] had decided the subject to specialize in future. Forty one (70.68%) chose surgery as their career choice. It was followed by Internal medicine- 35(60.34%), Anesthesia- 21(36.2%), Orthopedics- 19(32.75%) and Gynecology- 8(13.79%). Among the participants who chose anesthesia as their career choice, five (8.62%) stated anesthesia as their first career preference, three (5.17%) as their second and 13(22.41%) as their third career preference. The positive key attributes of choosing anesthesiology was mostly because they were interested in critical care 19(90.47%), satisfaction from the immediate result seen 15(71.42 %) and minimum patient contact 12(57.14%). The negative attributes of anesthesiology highlighted were risky job 23 (46.93%), lack of recognition by patient 13 (26.53%) and minimum patient contact 12 (24.48%). Conclusion: Findings suggests that perceptions of medical students towards anesthesiology are manifold. Duration of internship has biggest influence on motivating undergraduate students towards pursuing anesthesiology as a career.